Projection systems for future wood availability in Europe - Barreiro, Susana; Schelhaas, Mart-Jan (Natural Resources Institute Finland, Luke, 2016)
Information on sustainable wood supply potential in Europe is crucial for assisting forest industries and environmental policy makers. However, the variety of projection systems for forecasting wood availability makes the comparison of national results difficult. Under USEWOOD, a description of projection systems used in Europe has been compiled. The complexity of projection systems varies across Europe. Simple systems using forest management plans’ data combined with yield tables can be found as well as more complex tools based on National Forest Inventory (NFI) data. The latter may use species-specific climate sensitive growth models and are capable of integrating the effects of climate, management and disturbances. All tools are under constant improvement, although there is still a long way to go concerning the validation of projection systems. Few countries carried out sensitivity analyses on their tools and/or provide uncertainty measures. Notwithstanding, projection results should always be interpreted as what-if scenarios rather than seen as a prognosis.
Keywords: wood supply; projection systems; future scenarios; national forest inventory; USEWOOD